(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Ever since a decade, political advertisements are having a huge influence on voting behavior of younger and older people across the globe. These political advertisements through various mediums focus on persuading people in making their preferences (in choosing their representatives). This paper examines the impact of political advertisements on youth, with a sample size of 40 respondents, consisting Under Graduate and Post-Graduate students (age group 19-25), and their susceptibility to various political advertisements with respect to the voting behavior. The study area is Bangalore and the data is collected from the students pursuing their graduation and post-graduation in Jain University and the students for the sample study are chosen using simple random sampling method. Our findings extend the understanding of the effects of political advertisements on the voting behavior of Under-Graduate and Post-Graduate students with the help of cognitive and behavioral psychology. The results are mixed with respect to the influence made by political advertisements on youth. But specifically, with the emergence of political advertisements through new media, the impact has increased significantly. This study gives new direction for future studies in order to understand the psychology of youngsters.